Respuesta :

Cxlver

Answer:

(16, 30)

Step-by-step explanation:

First the equation of a circle is:

(x-h)^2 + (y-k)^2 = r^2, where (h,k) - the center.

We rewrite the equation and set them equal :

(x-h)^2 + (y-k)^2 - r^2 = x^2+y^2− 32x − 60y +1122=0

x^2 - 2hx + h^2 + y^2 - 2ky + k^2 - r^2 = x^2 + y^2 - 32x - 60y +1122 = 0

We solve for each coeffiecient meaning if the term on the LHS contains an x then its coefficient is the same as the one on the RHS containing the x or y.

-2hx = -32x => h = 16.

-2ky = -60y => k = 30. => the center is at (16, 30)

The centre of a circle is (16, 30).

The given circle equation is x²+y²−32x−60y+1122=0.

We need to find the centre of a circle for the given equation.

What is the standard form of the circle equation?

The standard form of the equation is (x-h)² + (y-k)² = r², where (h,k) is the center.

We rewrite the equation and set them equal:

(x-h)² + (y-k)² - r² = 0

x² +y² − 32x − 60y +1122=0

x² - 2hx + h^2 + y² - 2ky + k² - r² = x²  + y² - 32x - 60y +1122 = 0

We solve for each coefficient meaning if the term on the LHS contains an x then its coefficient is the same as the one on the RHS containing the x or y.

-2hx = -32x ⇒ h = 16.

-2ky = -60y ⇒ k = 30.

Therefore, the centre of a circle is (16, 30).

To learn more about the equation of a circle visit:

https://brainly.com/question/10165274.

#SPJ5